The Efficiency of Using K.W.L Strategy in Developing the Understanding Skills of Noble Hadith among Intermediate Grade Students in Makkah - Alsaadi, Alaa Humaiyed (Journal of Educational and Psychological Sciences, 2020)
The research aimed to know the effectiveness of using K.WL strategy for the development of understanding skills of The Prophet Traditions by the first intermediate grade students in Makkah.The research problem is identified the following main question:What is the effectiveness of use K.WL strategy for the development of understanding skills of The Prophet Traditions by thefirst intermediate grade students in Makkah?To answer the main question of research, the researcher used the quasi-experimental approach and the research's sampleconsisted of 60 female students from the first intermediate grade, then the researcher randomly divided them into twogroups: one is a trial which studied according to the K.W.L strategy and the other is a control group.To design the research's tool, it was designed a list of understanding skills of The Prophet Traditions, the researcher decided to choose the skills which had been agreed by 80% of the arbitrators, according to the list of understanding skills, the researcher had designed a test which measures the understanding skills of prophet traditions. After the researcher made sure of test's validity and reliability, the test had been pre and post applied.After the data of research had been analyzed by using arithmetic means, standard deviations, and T-test, the researcher concluded that there were statistically significant differences at the level of (0.01) in the dimensional measurement in modern skills, deductive and creative of prophet traditions understanding
Keywords: Efficiency; K.W.L Strategy; Understanding Skills